O Clã de Moreira Campos: aspectos sociais dos contos publicados em revista - Andrade, Lia Raquel Vieira de (2009)
It is well known that the central focus of writers from Ceará, mainly in prose or poetry, has been the cultural and social aspects of the region, they portrait costumes of the people, social problems and quite often the nature. This framework has been of great contribution to spread throughout Brazil the local literature, whose potential has been notably recognised by the literary critics. In particular, in the literature historiography, Ceará is one the most fertile grounds for literary groups such as the “Academia Francesa” (French Academy), the “Padaria Espiritual” (Spiritual bakery) and the “Grupo Clã” (Clan group). The Latest is perhaps one of the most relevant groups, due to the great variety of profiles arisen from it, indeed the Clan group gave birth to very distinctive artists such as fictionists, poets, essayist and literary critics, whom gave great contribution to the arts in Ceará and in Brazil. The group had an issue which was called “Revista Clã” (Clan Journal), which has been issued during forty years, therefore the there is a long source of literary, which deserves attention. One of the most appreciated members in the short-tale style is Moreira Campos, who published also essays and literary criticism in fifteen issues of the Journal. Some critics say Moreira Campos follows the thread of the great Machado de Assis and Graciliano Ramos, due to some common techniques, such as the concision, the irony and the critical representation of the society. In this work the short-tales which Moreira Campos published in the Clan Journal are studied by a textual analysis, in which we focus on the aspects used for social criticism, namely the construction of the characters and their lives.